Association Between Subjective Obesity Status and Smoking Behavior Among Normal-Weight Women. (June 2018) - Kim, Dae-Hwan
Smoking and obesity are chief causes of mortality, morbidity, and medical expenditure. However, few studies have investigated the linkage between subjective obesity status and smoking behavior. This study examines whether females in a normal body mass index range who perceive themselves as obese are more likely to smoke than those who do not perceive themselves as obese. Stratifying by age-group, I employed the propensity score matching analysis to control for selection bias. Although body mass index is lower for younger females aged 20 to 39, they are more likely than elder females to consider themselves as obese. Based on a logistic regression, my findings show that younger females who perceive themselves as obese are 21.2% more likely to smoke than females who do not perceive themselves as obese. The positive relationship between perceived obesity status and smoking behavior is also found in the propensity score matching analysis. However, the disparity in smoking prevalence is not detected between elder females who perceive themselves as obese and those who do not. Public education that fosters accurate perception of body shape is imperative in inducing healthy lifestyles and improving social welfare.